Efficacy of adjunctive antibiotics compared to non-antibiotic therapies following mechanical debridement for peri-implantitis: A systematic review and meta-analysis of randomized controlled trials - Caiyun Liu; Hongtao Wang; Yulan Li; Zhilong Huang; Jian Sun; Han Cai (PLoS ONE, 2026)
Objective To evaluate the efficacy of antibiotic therapy as an adjunct to mechanical debridement in peri-implantitis. Method PubMed, Embase, Web of Science, the Cochrane Library, and Scopus were searched (inception to 15 January, 2026). Additionally, clinical trials were searched on ClinicalTrials.gov. Meta-analyses were performed to evaluate bone level (BL), bleeding on probing (BOP), probing pocket depth (PPD), clinical attachment level (CAL), modified plaque index (mPLI), plaque score (PS). Results Twenty-two RCTs were included. Adjunctive antibiotics with mechanical debridement demonstrated significant advantages in improving PPD (WMD = −0.69; 95% CI: [−1.04, −0.33]; P = 0.0001; heterogeneity:I 2 = 91%, P < 0.00001), CAL (WMD = −0.55; 95% CI: [−1.07, −0.04]; P = 0.04; heterogeneity:I 2 = 95%, P < 0.00001), PS (WMD = −4.07; 95% CI: [−6.80, −1.33]; P = 0.004; heterogeneity:I 2 = 0%, P = 0.94), and BOP (WMD = −12.45; 95% CI: [−24.13, −0.77]; P = 0.04; heterogeneity:I 2 = 94%, P < 0.00001). In the subgroup analysis comparing mechanical debridement plus antibiotics versus mechanical debridement alone, statistically significant improvements were observed for CAL (WMD = −0.84; 95% CI: [−1.55, −0.13]; P = 0.02) and PS (WMD = −3.94; 95% CI: [−7.14, −0.74]; P = 0.02), confirming clinical necessity of antibiotics as an adjunct to debridement. In the comparison of local versus systemic antibiotic administration, comparable efficacy in reducing PPD was observed for both local (WMD = −0.68; 95% CI: [−1.14, −0.22]; P = 0.004) and systemic (WMD = −0.70; 95% CI: [−1.25, −0.15]; P = 0.01) routes, with no significant difference between subgroups (P = 0.95, I² = 0%). For PS, local antibiotics (WMD = −6.57; 95% CI: [−11.10, −2.04]; P = 0.004) demonstrated significantly greater improvement compared to systemic antibiotics (WMD = −2.63; 95% CI: [−6.07, 0.80]; P = 0.13). Conclusion As an adjunct to mechanical debridement, antibiotics may provide modest benefits for peri-implantitis, demonstrating efficacy in improving probing pocket depth, clinical attachment level, plaque score, bleeding on probing, and other parameters related to soft tissue health and plaque control. PROSPERO CRD420261328879. Available from https://www.crd.york.ac.uk/PROSPERO/view/CRD420261328879 .